Prefilled devices for parenteral applications. (March 2014) - Gurman, Pablo; Chi, Albert; Hood, Tiffany; Reina, Micaela; Rosen, Yitzhak; D'hers, Sebastian; Elman, Noel
Abstract : Current parenteral administration of drugs suffers from several drawbacks including the requirement of healthcare personnel to administer the drug, the risk of needle stick injuries that may result in the transmission of blood borne pathogens, and patient discomfort. Prefilled devices have emerged as powerful tools to improve parenteral administration of drugs. There are a number of clinical conditions including treatment of endocrine diseases, neurological disorders, autoimmune diseases and emergency medicine where prefilled devices have made major improvements to patient care. Prefilled devices have become an important set of tools for the medical practitioner due to their ease of use and safety, cost effectiveness and patient convenience. This review provides a comprehensive summary of existing prefilled devices, their current clinical uses and corresponding regulatory processes.